Replace all occurrences of in with .

Simplify .

Apply the distributive property.

Multiply.

Multiply by .

Multiply by .

Remove any equations from the system that are always true.

Solve by Substitution y=3x-4 -3y=-9x+12

Skip to content
# Solve by Substitution y=3x-4 -3y=-9x+12

Replace all occurrences of in with .

Simplify .

Apply the distributive property.

Multiply.

Multiply by .

Multiply by .

Remove any equations from the system that are always true.

Solve by Substitution y=3x-4 -3y=-9x+12